Tindak Pidana Perzinaan Dalam Perspektif Perbandingan Antara Kitab Undang-Undang Hukum Pidana Dan Hukum Pidana Islam - Rahmawati Rahmawati (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2012)
In essence,the act orcrimeof adulteryshall containthe followingelements: The deedsdonearenot aproperhusband and wifewho havenoreligioustieslegitimateand legalandillegalnature, the act of intercoursebetweenmen and women thatthere is nomarriage,an act which isforbiddenworshipGod andcharityare notacceptable to GodAlmightyfor yearsandGodhatesthose whocommit adultery.